2011
DOI: 10.1590/s1807-59322011000900015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of angiogenic factors and cyclooxygenase-2 expression in cartilaginous tumors – clinical and histological correlation

Abstract: OBJECTIVES:To study the role of angiogenesis and cyclooxygenase-2 expression in cartilaginous tumors and correlate these factors with prognosis.INTRODUCTION:For chondrosarcoma, the histological grade is the current standard for predicting tumor outcome. However, a low-grade chondrosarcoma can follow an aggressive course—as monitored by sequential imaging techniques—even when it is histologically indistinguishable from an enchondroma. Therefore, additional tools are needed to help identify the biological potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Cintra et al (2011) investigated the role of COX-2 expression and angiogenetic factors in chondrosarcoma progression. The authors observed that a high COX-2 expression adversely affects patient survival and a positive correlation between CD34 and COX-2 expression, which confirms the relationship between COX-2 and angiogenesis, suggesting a possible role for this marker in patient prognosis (Cintra et al, 2011).…”
Section: Chondrosarcomamentioning
confidence: 99%
“…Cintra et al (2011) investigated the role of COX-2 expression and angiogenetic factors in chondrosarcoma progression. The authors observed that a high COX-2 expression adversely affects patient survival and a positive correlation between CD34 and COX-2 expression, which confirms the relationship between COX-2 and angiogenesis, suggesting a possible role for this marker in patient prognosis (Cintra et al, 2011).…”
Section: Chondrosarcomamentioning
confidence: 99%
“…Chondrosarcoma is the third most common primary bone cancer . Based on cellularity, nuclear atypia, and pleomorphism, chondrosarcoma is histologically classified into three grades including low grade (grade 1), intermediate grade (grade 2), and high grade (grade 3) . Wide surgical resection is the most common treatment choice for chondrosarcoma .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Also, expansion in small bones, a diaphyseal location, superficial scalloping, septonodular enhancement on MRI, a size less than 5 cm in long bones, and even some increase in size are consistent with the diagnosis of enchondroma. 14,16,[18][19][20][21][22][23][24][25] Fortunately, the clinically more relevant differentiation between ACTs and grade 2 or higher CSs is more reliable on imaging (and histology). 14,16,[18][19][20][21][22][23][24][25] Fortunately, the clinically more relevant differentiation between ACTs and grade 2 or higher CSs is more reliable on imaging (and histology).…”
Section: New Practicementioning
confidence: 99%
“…27 MRI is the method of choice for displaying not only these radiographic features (with the exception of calcifications) but also features of high-grade CS, such as abundant (>50%) mucoid (which has a high signal intensity on fluid-sensitive MRI sequences), cortical thickening (also well seen on radiographs and computed tomography), cortical destruction, soft-tissue extension, perilesional inflammatory reactions in bone and soft tissue, and periostitis. 20,21,23 With these parameters, the diagnostic accuracy of MRI is greater than 90%. 20,21,23 With these parameters, the diagnostic accuracy of MRI is greater than 90%.…”
Section: New Practicementioning
confidence: 99%